2015
DOI: 10.2217/whe.15.4
|View full text |Cite
|
Sign up to set email alerts
|

Weight Gain After Oophorectomy Among Women with a BRCA1 or BRCA2 Mutation

Abstract: Aim:To measure weight gain among unaffected women with a BRCA1 or BRCA2 mutation after undergoing an oophorectomy. Patients & methods: We compared the bodyweight of women with (n = 405) and without an oophorectomy (n = 741) at baseline as well as the rate of weight change prior to and following surgery among 1454 BRCA mutation carriers who had an oophorectomy. Results: There was a small and non-significant difference in bodyweight between BRCA mutation carriers who had an oophorectomy compared with those women… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
2
1
0
Order By: Relevance
“…Our findings support those of the Framingham Heart Study which demonstrated that although postmenopausal women have increased weight and visceral adipose tissue than younger women, this association is predominately due to age rather than menopause ( 17 ). It also supports the findings of Kotsopoulos et al, who found that oophorectomy in women with BRCA 1 and BRCA 2 mutation was not associated with significant weight gain ( 7 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings support those of the Framingham Heart Study which demonstrated that although postmenopausal women have increased weight and visceral adipose tissue than younger women, this association is predominately due to age rather than menopause ( 17 ). It also supports the findings of Kotsopoulos et al, who found that oophorectomy in women with BRCA 1 and BRCA 2 mutation was not associated with significant weight gain ( 7 ).…”
Section: Discussionsupporting
confidence: 90%
“…Women at elevated risk of ovarian cancer must balance the established risks of RRSO for cancer risk reduction with the potential adverse sequelae of surgical menopause ( 4-6 ). In clinical practice, concerns of women contemplating RRSO include weight gain and change in body composition postsurgery ( 7-10 ).…”
mentioning
confidence: 99%
“…Thus, the effect of gonadectomy is consistent with sex-neutral obesity development in Mito-Ob, as observed previously during their phenotypic characterization [ 14 ]. Wild-type mice started to gain weight after gonadectomy, supporting previous reports that indicated the absence of gonadal estrogens or androgens led to weight gain in rodents and humans with aging [ 29 31 ]. However, this change was not found to be associated with adipose tissue area.…”
Section: Discussionsupporting
confidence: 85%